The The impacts of blended corpus-based instruction on enhancing writing proficiency of Thai university students - Satchayad, Patcharin; Charubusp, Sasima (English Language Teaching Educational Journal, 2023)
Collocational competence is gaining more attention in the field of second language acquisition as it indicates a higher level of target language proficiency. However, Thai university students have been reported as obtaining a low degree of collocational competence which affects productive second language writing (Boonyarattanasoonthorn et al., 2020). The current study aimed to examine the impacts of blended corpus-based instruction (BCBI) on enhancing Thai university students’ writing proficiency and to examine the students’ attitudes towards the implementation of BCBI. A mixed-methods one-group experimental study was conducted with 43 first-year English major students at an autonomous university in Thailand for 8 weeks. The data were gathered utilizing a pre-test, a post-test, an attitude questionnaire, and a semi-structured interview. The results revealed significant differences between the scores before and after the implementation of BCBI at 0.05. Despite there being no drastic change in their collocational competence, the students were highly positive towards the instruction, in particular the use of corpus-based data to assist their writing as well as the awareness of gaining collocational competence. To effectively integrate corpus-based instruction into a writing pedagogy, tasks should be manageable and achievable by the students.